ANALISIS PENINGKATAN KUALITAS PRODUK DAN PELAYANAN JASA TERHADAP KEPUASAN PELANGGAN PADA PT TELKOM AKSES MEDAN - Nailul Muna; Nuri Aslami (Transpublika Publisher, 2022)
PT. Telekomunikasi Indonesia, Tbk or commonly referred to as TELKOM is a state-owned company engaged in telecommunications and network services in the territory of Indonesia. As a state-owned company whose shares are traded on the stock exchange, the majority shareholder of the company is the Government of the Republic of Indonesia while the rest is controlled by the public. The largest state-owned TIMES (Telecommunication, Information, Media, Education and Service) business provider company in Indonesia, which is a more complete business portfolio following the changing trends of global business in the future. This study aims to determine how to improve products and services on customer decisions at PT Telkom Access Medan. The method used in this research is to use a qualitative method by calculating the number of consumer responses using a questionnaire. This case describes consumers at PT. Tekom Access Medan which requires attention and service to its customers, both in terms of product quality and service, so that customers can increase their level of satisfaction with the use of IndiHome products.